Programa de prácticas pre profesionales para la formación de los estudiantes de la carrera de Ciencias de la Educación mención Educación Básica de la Universidad Técnica de Cotopaxi. - Viera Zambrano, Angel Manuel Rodrigo (2015)
The Ecuadorian state has to ensure high quality training that will tend to excellence and relevance System of Higher Education, Science Education Major Mention Basic Education at the Technical University of Cotopaxi has the purpose to form professionals capable of analyzing, plan, manage and evaluate models and intervention strategies in professional fields associated with basic sciences, social, and education. The training of future teachers will be done according to the organization of learning, which involves planning the student's learning process through learning activities with teaching, practical application and selfemployment that guarantee relevant results in various levels of training and modalities. (Art. 10. Academic Regulation Regime. RRA) .Nowadays the problem that has the Basic Education Major is the lack of a pre-professional practice program based on the Regulation of Academic System to develop this research was used the types as: qualitative, quantitative, bibliography and field research methods and techniques, which enabled them to obtain information and data of the object and study population. The administrators, teachers, students of the Major, guiding teachers of educational institutions are strongly agreed that pre practice program is designed. The objective of the proposal is to design the pre professional practice program to strengthen the training of students. The preprofessional practices are an essential part of the curriculum and learning activities are aimed at the application of knowledge and skills development and specific skills that a student must acquire for adequate performance in their future profession. (Art. 88. RRA).